REMOTE LABORATORY BERBASIS PROTOKOL VIRTUAL NETWORK COMPUTING SEBAGAI MEDIA PEMBELAJARAN JARAK JAUH PROGRAMMABLE LOGIC CONTROLLER - Rachman, Isa; Hasin, Muhammad Khoirul; Adhitya, Ryan Yudha; Rahmat, Mohammad Basuki; Adianto, Adianto; Nurcahyo, Agus; Ruwahida, Dewi Rizani (Telkom University, 2023)
One effective method that can be applied to online practical learning during the COVID-19 pandemic is remote laboratory which is a combination of the real world and the virtual world using the internet network. This research aims to design remote laboratory based on the Virtual Network Computing (VNC) on Programmable Logic Controller (PLC) which is one of the regular practical devices used in Industrial Automation Laboratory. Remote laboratory in the form of a remote laboratory website for administrators consisting of user management and course management; and for users it consists of login, course and schedule, user order and remote desktop containing PLC Trainer, XG5000 and camera. From the results of remote laboratory testing starting from registration, remote laboratory website, login, course selection, suitability of course schedules, user order and remote desktop can be accessed so that the designed remote laboratory can work properly. The existence of a delay time of 0,52–1,73 seconds for the results of shooting by the camera as a display visualization for online monitoring of practice activities in the laboratory on the client computer is influenced by the condition of the internet network used mainly on server computers. Key Words: practice, online, remote, laboratory, VNC, PLC.